2013
DOI: 10.1089/ars.2012.4922
|View full text |Cite
|
Sign up to set email alerts
|

Examining and Mitigating Acellular Hemoglobin Vasoactivity

Abstract: Significance: There has been a striking advancement in our understanding of red cell substitutes over the past decade. Although regulatory oversight has influenced many aspects of product development in this period, those who have approached the demonstration of efficacy of red cell substitutes have failed to understand their implication at the level of the microcirculation, where blood interacts closely with tissue. Recent Advances: The understanding of the adverse effects of acellular hemoglobin (Hb)-based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 167 publications
0
19
0
Order By: Relevance
“…Second, acellular Hb enhances hyper-oxygenation of the tissues as O 2 is both dissolved and bound to Hb in the plasma, triggering autoregulatory metabolic mechanisms that induce vasoconstriction to limit blood flow (35). Third, acellular Hb extravasates through the endothelial lining, deposits in the interstitial space and undergoes uncontrolled autoxidation processes, forming methemoglobin (metHb), reactive O 2 species, and inflammation and vascular damage, hence affecting vascular function and diameter (36, 37). Independent of whatever underlying mechanism is ultimately responsible, it is clear that an increase in HBOC concentration results in increased vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…Second, acellular Hb enhances hyper-oxygenation of the tissues as O 2 is both dissolved and bound to Hb in the plasma, triggering autoregulatory metabolic mechanisms that induce vasoconstriction to limit blood flow (35). Third, acellular Hb extravasates through the endothelial lining, deposits in the interstitial space and undergoes uncontrolled autoxidation processes, forming methemoglobin (metHb), reactive O 2 species, and inflammation and vascular damage, hence affecting vascular function and diameter (36, 37). Independent of whatever underlying mechanism is ultimately responsible, it is clear that an increase in HBOC concentration results in increased vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…It is produced through the polyethylene glycol modification (PEGylation) of surface lysine residues on purified bovine Hb with 5000 Da PEG‐succinimidyl carbonate followed by carboxylation. Due to its hydrophilic nature, PEG increases the effective molecular size of Hb and inhibits its interaction with the vascular endothelium . PCHB was well tolerated by 18 healthy human volunteers in a Phase I clinical trial and was shown in preclinical trials to protect the myocardium against ischemia–reperfusion injury in diabetic and normal mice .…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] Further accumulation of oxy-Hb in the bloodstream will be filtered out by the kidney glomeruli and reabsorbed by the tubules (Scheme 8). [25] Overloading this system will result in oxidative damage and cell death within the kidneys. Additionally, upon dissociation of the oxy-Hb tetramer, the oxy-Hb dimers and monomers will be able to penetrate in between the endothelial cells lining the blood vessels due to their small size (Scheme 1C, 9).…”
Section: Accepted Manuscriptmentioning
confidence: 99%